Entrepreneurial Behavior of Piggery Trainees of Pashu-Vigyan Incubator - Anna, Akriti; Singh, B. P.; Chander, Mahesh; Sagar, M. P.; Suman, R. S.; Pawale, S. S. (Indian Journal of Extension Education, 2022)
Entrepreneurship as a dynamic and innovative process of a country’s development has become a prerequisite for supporting the government of India’s ambitious flagship program of ‘Atm-nirbhar Bharat”. The study is an ex-post facto research to ascertain the entrepreneurial behavior of the trainees who attended the entrepreneurship development programme on piggery at agri-business incubator ICAR-IVRI (Pashu-Vigyan Incubator). A purposive sampling technique was used to select 80 trainees starting their piggery enterprises. The data were collected through mailed e-questionnaire and telephonic follow-up. The entrepreneurial behavior was determined on nine dimensions and majority of the trainees showed a high level of ‘cosmopoliteness’, ‘achievement motivation’, ‘risk orientation’ and coordinating ability but possessed medium level ‘information seeking behavior’, ‘self-confidence’, ‘innovativeness’, ‘planning ability’. The entrepreneurial behavior showed positive and significant correlation with their experience in piggery, attitude towards scientific piggery farming, social participation, education and income. Overall high mean entrepreneurial behavior index was observed indicating a positive effect of the Entrepreneurship Development Program.
Keywords: Entrepreneurs; Entrepreneurship development; Pig farming; Piggery enterprises